Improved Cerebral Arteriovenous Malformation Obliteration With 3-Dimensional Rotational Digital Subtraction Angiography for Radiosurgical Planning: A Retrospective Cohort Study. Issue 1 (27th July 2020) - Anderson, Joshua L; Khattab, Mohamed H; Sherry, Alexander D; Luo, Guozhen; Chitale, Rohan V; Froehler, Michael T; Fusco, Matthew R; Cmelak, Anthony J; Attia, Albert
Abstract: BACKGROUND: Stereotactic radiosurgery (SRS) for cerebral arteriovenous malformations (AVMs) is well-established. Radiographic advantages exist for 3-dimensional rotational digital subtraction angiography (3DRA) over 2-dimensional digital subtraction angiography (2D DSA) in delineating AVM nidus structure for SRS treatment planning. However, currently there is limited to no data directly comparing 2D DSA versus 3DRA in terms of patient outcomes. OBJECTIVE: To investigate whether the use of 3DRA over 2D DSA in radiosurgical treatment planning for AVMs associates with improved clinical outcomes. METHODS: All AVM patients treated with SRS at our institution between the years 2000 and 2018 were identified. Primary outcomes were obliteration rates and time to obliteration (TTO); secondary outcomes included rates of post-SRS hemorrhage, salvage therapy, and symptomatic radionecrosis. A minimum of 12 mo of follow-up imaging/angiogram post-SRS was required, or alternatively evidence of obliteration on angiogram prior to 12 mo post-SRS. Single predictor and multivariable Cox regression and logistic regression models were constructed to test for association between radiographic, clinical, and treatment factors with outcomes. RESULTS: A total of 75 patients were included. Total 17 patients received 3DRA and 58 patients received 2D DSA, with a median follow-up of 3.29 yr. The 3DRA is significantly associated with improved TTO on single predictor (HR 2.87, 1.29-6.12; P = .0109) and multivariable analysis (HR 2.448, 1.076-5.750; P = .0330) and increased odds of achieving obliteration by 3 yr post-SRS on single predictor analysis (OR 6.044, 1.405-26.009; P = .0157). CONCLUSION: The 3DRA over 2D DSA in SRS treatment planning for AVMs may result in improved TTO and 3-yr obliteration rates. Further investigation and prospective study are warranted. Graphical Abstract: